Analisis Faktor-Faktor yang Mempengaruhi CSR Disclosure Pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2016-2018 - Utamie, Dara Nida; Akram, Akram; Nugraha Ardana Putra, I Nyoman (E-Jurnal Akuntansi, 2020)
The research aims to analyze the Audit Committee, Profitability, Company Size and Leverage on CSR Disclosure. The study population is manufacturing companies listed on the Stock Exchange in 2016-2018 which reveal annual reports and CSR reports. The sample was determined by purposive sampling and 342 observations were obtained. Research data were analyzed using multiple linear regression methods. The research findings show that the Audit Committee, Profitability and Company Size have a positive and significant effect on Corporate Social Responsibility Disclosure, while leverage has a negative and not significant effect on CSR. The implication of this research is that CSR needs to be made as one of the company's long-term strategic tools which in turn can benefit stakeholders so that it can be considered by investors in making decisions. Keywords: Audit Committee; Profitability; Company Size; Leverage; CSR Disclosure